Code Mixing and Code Switching in a Korean-Song Lyric (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
In social life, language is crucial where all people use it as the way to communicate each other. As one of the ways to communicate, song is a means to convey expression. The objectives of this study are as follows; (1) to identify code mixing and code switching in the every lyric of Red Velvet’s song entitled Taste; (2) to classify the types of code mixing as well as code switching found in the lyric of Red Velvet’s song Taste. This is a descriptive qualitative study that describes the significance of code mixing and code switching stated in the lyric of Red Velvet’s song Taste. The results of this study are (1) there are 9 code mixing and 11 code switching in Korean song lyric Taste by Red Velvet (2) the kinds of code mixing, 8 intra-sentential mixing and 1 involving a change of pronunciation. Also The kinds of code switching 8 inters-sentential switching, 1 emblematic switching, and 2 establishing continuity with the previous speaker. So, the theory of code mixing and code switching analysis from Crystal (2008) and Wardhaugh (2006) is stick with the result of code mixing and code switching found in Korean song lyric Taste by Red Velvet.